P573 Real-world effectiveness and safety of vedolizumab and anti-TNF in biologic-naive ulcerative colitis patients: Results from the EVOLVE study. (25th January 2019) - Yarur, A; Mantzaris, G; Silverberg, M; Walshe, M; Zezos, P; Stein, D; Bassel, M; Lissoos, T; Lopez, C; Natsios, A; Radulescu, G; Patel, H; et al.
Abstract: Background: This study aimed to compare the real-world clinical effectiveness and safety of vedolizumab (VDZ), a gut-selective anti-α4β7-integrin, and anti-tumour necrosis factor (TNF) agents in biologic (bio)-naïve ulcerative colitis (UC) patients. Methods: A retrospective chart review study was conducted in adult (≥18 years), bio-naïve UC pts treated with VDZ or anti-TNF (June 2014 to February 2018) in Canada, Greece and the USA. Data were collected from treatment (Tx) initiation to earliest of death, chart abstraction date or 6 months post-Tx discontinuation. Cumulative rates of clinical response, clinical remission, mucosal healing, Tx persistence and dose escalations were estimated over 24 months (Kaplan–Meier method). Incidence rates (per 100 person-years [PYs]) of UC exacerbations, colectomy, serious adverse events (SAEs) and serious infections (SIs) were assessed. A Cox proportional hazards model was used to compare outcomes with adjustments for baseline confounders: age, sex, albumin, C-reactive protein, disease location and duration, UC-related hospitalisations (prior 12 mo) and disease severity; adjusted hazard ratios (HR) with 95% confidence interval are reported. Results: Overall, 527 UC patients (VDZ: 325; anti-TNF: 202 [adalimumab: 58, infliximab: 120, golimumab: 24]) from 37 sites were included (median [min–max] follow-up [mo]: VDZ, 16.1 (3.0–47.0); anti-TNF, 20.0 [3.5–50.6]). Baseline characteristics are shown in Table 1. At 24 months, cumulative rates of clinical response (91% vs. 86%), clinical remission (79% vs. 66%) and mucosal healing (92% vs. 84%) were high in VDZ and anti-TNF patients, respectively, and did not differ significantly between groups. Higher Tx persistence (75% vs. 54%; p < 0.0001) and similar rates of dose escalations (25% vs. 31%; p < 0.05) occurred in VDZ vs. anti-TNF patients. The incidence rate (per 100 PYs) of UC exacerbations (28.3 vs. 43.9) and SAEs (4.9 vs. 10.4) were significantly ( p < 0.05) lower in VDZ vs. anti-TNF patients but similar for colectomy (1.8 vs. 2.2) and SIs (1.9 vs. 2.2). Adjusted HR for outcomes are shown in Table 2. Conclusions: VDZ and anti-TNF have similar rates of clinical effectiveness in bio-naïve UC patients in real-world clinical practice. Bio-naïve UC patients receiving VDZ are significantly more likely to persist with Tx and experience fewer exacerbations and SAEs than anti-TNF patients.